2023
DOI: 10.47191/ijmra/v6-i6-28
|View full text |Cite
|
Sign up to set email alerts
|

Green Finance and Bank Performance: Evidence from Bangladesh

Abstract: The severe repercussions of the global climate catastrophe are being felt all across the world. Each industrialized and developing country must take action in response to the consequences of global climate change that endanger life on our planet. This study looks into how green finance has affected Bangladeshi private commercial banks' financial performance. For eight years, from 2014 to 2021, all private commercial banks are surveyed quarterly for secondary data. The performance of the banks is evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Secondly, there is a lack of incentives from governments and stakeholders to promote green investment, which poses a challenge for the implementation of sustainable finance (Bhalla, 2023). Additionally, the focus on traditional financial performance metrics may overshadow the importance of green finance in enhancing a bank's financial performance (Chowdhury, 2023). Furthermore, the complexity of integrating green finance practices into existing banking operations and products may deter researchers from exploring this area (Aulia et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, there is a lack of incentives from governments and stakeholders to promote green investment, which poses a challenge for the implementation of sustainable finance (Bhalla, 2023). Additionally, the focus on traditional financial performance metrics may overshadow the importance of green finance in enhancing a bank's financial performance (Chowdhury, 2023). Furthermore, the complexity of integrating green finance practices into existing banking operations and products may deter researchers from exploring this area (Aulia et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…One is to examine the impact of green finance on the financial performance of banks. Previous studies have shown that green finance has a positive effect on return on equity, net interest margin, and net non-performing loans to total loans ratio (Chowdhury, 2023). Another perspective includes customer perception and awareness of green banking.…”
Section: Discussionmentioning
confidence: 99%